A new species of Cinnamomum (Lauraceae) from Nilgiris, southern Western Ghats, India - Geethakumary, M P; Pandurangan, Alagramam Govindasamy; Deepu, S (Phytotaxa, 2015)
A new species of Cinnamomum (Lauraceae), C. nilagiricum is described and illustrated on the basis of distinct morphological characters known from Nilgiris, southern Western Ghats, India.  It is allied to C. dubium but differs in the nature of trunk; shape, size and smell of leaves; 4-locellate anthers of whorl III stamens etc.  A detailed description, distribution, phenology, illustration, colour plates and relevant notes are provided.